Talking food: A conversation about Zimbabwe, cooking, eating and social living - Wardrop, Joan; Bonzo, G.; Kitson, N. (The University of Western Australia, 2000)
'Sadza' is considered almost a sacred food and a meal is not a meal without it... by the time they are about 10 years old, most Shona kids have learned to cook sadza. People are judged on how well they cook sadza: it is not a simple task (because it can get lumpy or too hard or soft) and some women never learn to do it properly and are spoken about because of this. Parents are very proud when their children can cook 'sadza' and give them a lot of practice.